NIÑEZ, POBREZA Y ESTRATEGIAS DE SOBREVIVENCIA. FAMILIAS CAMPESINAS DEL VALLE CENTRAL Y GUANACASTE, COSTA RICA (1912-1970) - Menjívar Ochoa, Mauricio (2008)
The article analyzes the poverty conditions lived by boys and girls of peasant families, the role that children had in the family subsistence strategies as well as the implications of the poverty and those strategies upon their lives.  The period of analysis covers from 1912 to 1970.  For such effects a qualitative analysis of rural women and men biographies from the Central Valley and North Pacific of Costa Rica is carried out. The research shows deficiencies in housing, alimentation, education and health faced by families. These lacks were aggravated by the scarce family incomes and the high number of members, the distance of the population centers as well as the lack of educational and sanitary infrastructure.  The research also shows that the incorporation of children and girls to work was a strategy of great importance for the family in order to survive.  However, their work did not result in the overcoming of poverty.  Finally, the study finds that boys and girls labor was consistent with sexual division of work, reinforcing their gender identities. The poverty affected the health and the bodies of boys and girls, limited their educational projects and, in combination with dominant conceptions of gender, reinforced the sexual division of labor.